Differences in laboratory requesting patterns in emergency department in Spain. (July 2013) - Salinas, Maria; López-Garrigós, Maite; Uris, Joaquín; ,
Background: It is necessary to achieve a reduction in the number of requests for laboratory tests by improving the appropriateness of testing behaviour. The aim of the study was, first, to compare laboratory requiring patterns for emergency department (ED) patients in clinical laboratories of different institutions in Spain; second, to design an appropriateness pre-pre-analytical quality control report based on appropriateness indicators. Methods: A call for data was posted on a website. We obtained production statistics for the year 2010 from emergency laboratories at 36 hospitals. Two types of appropriateness indicators were calculated: test request per 1000 ED admissions or related test requesting ratios. In order to explore the inter-practice variability in tests requests, the 'index of variability' was calculated. A pre-pre-analytical quality control report was designed, prepared and sent to each participating laboratory. The savings generated, if each Health-care Department would have achieved the appropriate indicator standard, were calculated. Results: The rate of request of the stat tests ranged from 44 to 412 per 1000 ED patient admissions. There was a high and peculiar dispersion of related test requesting ratio results. If every single laboratory would have achieved the appropriate indicator, we would have saved 1, 019, 230 urea, 302, 511 AST and 316, 161 CK unnecessary tests. Conclusions: There are large variations of test requesting in the emergency setting. An appropriateness pre-pre-analytical quality control report was useful for comparing requesting patterns. The study shows the need to unify demand. The key to achieve this goal will be interdepartmental cooperation between ED clinicians and laboratory professionals.